Audit Committee And Earnings Management: The Role Of Gender - Widya. A. Sudarman; Suzy Noviyanti; Jony Oktavian Haryanto; Lanita Winata (Jurnal Akuntansi, 2019)
This study has a purpose to investigate the effect of committee audit on earnings management. Using a sampel of companies companies listed in Indonesia Stock Exchange (IDX) 2013-2017. Results of this study shows that gender of audit committee significantly effect earnings management, it explains that female on audit committee are more careful and allow for discretion in terms of financial reporting. The results explain gender theory that women are more risk averse and ethical than men. This research provides new insights for management so that they can consider gender in the selection of committee audit to be appointed by the company with regard to the financial reporting process.